1999
DOI: 10.1016/s0031-9422(99)00271-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope ratios of amylose, amylopectin and mutant starches

Abstract: Carbon isotope ratios (expressed as d 13C values) were determined for various sources of starch and the starch fractions amylose and amylopectin. The d13 C values of amylose were consistently less negative, 0.4±2.3 -, than those of amylopectin in kernal starch from maize (Zea mays ) and barley (Hordeum vulgare ) and in tuber starch from potato (Solanum tuberosum ). Kernel starch isolated from the maize mutants wx1 and ae1, with known genetic lesions in the starch biosynthetic pathway, also showed signi®cant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Differences in δ 13 C background levels between n -alkanes ( Table 2 ) appeared to depend on the respective chain length and suggest that carbon isotope discrimination occurs during the enzymatic n -alkane biosynthesis by decarbonylase in the plant cuticula. Similar observations were reported for the biosynthesis of lignin [30] and starch [31] in plant tissue. Differential carbon allocation as observed in the plant tissue does not occur in the animal organism due to the absence of ruminal synthesis and degradation of n -alkanes [10], [11].…”
Section: Discussionsupporting
confidence: 89%
“…Differences in δ 13 C background levels between n -alkanes ( Table 2 ) appeared to depend on the respective chain length and suggest that carbon isotope discrimination occurs during the enzymatic n -alkane biosynthesis by decarbonylase in the plant cuticula. Similar observations were reported for the biosynthesis of lignin [30] and starch [31] in plant tissue. Differential carbon allocation as observed in the plant tissue does not occur in the animal organism due to the absence of ruminal synthesis and degradation of n -alkanes [10], [11].…”
Section: Discussionsupporting
confidence: 89%
“…However, solubilization by DMSO yielded starch preparations that were depleted in 13 C compared to untreated controls, while samples derived by HCl dissolution and ethanolic precipitation were always 13 C enriched (Table 1). Recently, it has been shown that δ 13 C values of amylose were consistently less negative than those of amylopectin by up to 2.3‰,9 suggesting that HCl and DMSO exhibit different efficiencies in solubilizing amylose and amylopectin.…”
Section: Resultsmentioning
confidence: 99%
“…Native starches from potato ( Solanum tuberosum L.), rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.) were purchased from Merck (Darmstadt, Germany). All starch samples were pre‐washed three times with methanol/chloroform/water (MCW, 12:5:3, v/v/v) to extract traces of lipids and other low‐molecular‐weight substances, and dried before further use 9. Heat‐stable α‐amylase from Bacillus licheniformis was purchased from Sigma‐Aldrich Chemicals (Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…We did not detect this relationship in our study, but the δ 13 C of starch and total bulk needle material of 1-yearold spruce needles did show a positive correlation to temperature for 2 consecutive years. The best correlation was found for climate data collected during the month before sampling, indicating that starch is a temporal medium-term integrator of δ 13 C. However, the temperature signal is not strongly reflected in the δ 13 C signature and, in the case of starch, could be superimposed by enzyme fractionation (Gleixner et al 1993;Scott et al 1999).…”
Section: Relationship Between δ 13 C and Climatic Factorsmentioning
confidence: 96%
“…2A, B) (Brugnoli et al 1988;Jordan and Mariotti 1998;Duranceau et al 1999). This difference results from isotopic fractionation by enzymes (Scott et al 1999).…”
Section: Relationship Between δ 13 C and Climatic Factorsmentioning
confidence: 99%